The Role of Notaries in Drafting Fiduciary Guarantee Deeds over Intellectual Property: Challenges in Verification and Economic Valuation - Fania, Novianda; Noval, Sayid Muhammad Rifki; Kencanawati, Erny (Magister Kenotariatan Universitas Pasundan, 2025)
This study analyses the role of Notaries in drafting fiduciary guarantee deeds with intellectual property as collateral, and the challenges encountered in verification and economic valuation. Problems arise because some Notaries face obstacles in preparing intellectual property guarantee deeds due to limited experience, complex document requirements, and difficulties verifying ownership. This study employs a normative juridical method, drawing on statutory and conceptual approaches. Secondary data were obtained from primary legal materials, including legislation, and from secondary legal materials comprising relevant legal literature. The findings indicate that Notaries play a central role in ensuring legal certainty by preparing authentic deeds, registering fiduciary guarantees, and processing fiduciary guarantee certificates. Notaries also act as authorized representatives to register fiduciary guarantees on behalf of fiduciary recipients. The main challenges faced by Notaries include verifying the registration status of intellectual property with the Ministry of Law and Human Rights, understanding the specific characteristics of intangible intellectual property, and assessing the economic value, which is often subjective and fluctuating. This study concludes that Notaries need to apply the principle of prudence by ensuring that intellectual property licenses are documented in notarial deeds, carefully verifying ownership and legal status, and considering potential infringement risks against the collateral objects.